Northern Arts The Breakthrough of Scandinavian Literature and Art, from Ibsen to Bergman - Weinstein, Arnold (Princeton University Press, 2021)
Northern Arts is a magnificent and provocative exploration of Scandinavian literature and art. With intellectual power and deep emotional insights, writer and critic Arnold Weinstein guides us through the most startling works created by the writers and artists of Scandinavia over the past two centuries. Here readers will gain new perspectives on canonical giants such as Søren Kierkegaard, Henrik Ibsen, August Strindberg, Edvard Munch, Knut Hamsun, and Ingmar Bergman. Readers will also encounter popular favorites like children's writer Astrid Lindgren, and come to know the work of lesser-known masters such as the novelist Tarjei Vesaas and the painters Ernst Josephson and Lena Cronqvist. Weinstein uses the concept of "breakthrough"--boundary smashing, restlessness, and the exploding of traditional forms and values--as a thematic lens through which to expose the roiling energies and violence that course through Scandinavian literature and art. Defying preconceptions of Scandinavian culture as depressive or brooding, Weinstein invites us to imagine anew this transformative and innovative tradition of art that continually challenges ideas about the sacred and the profane, family and marriage, children, patriarchy, and personal identity. Through these works he brings us face-to-face with our most hidden selves and urges, enriching our understanding of the emotions and forces that govern our lives. Northern Arts is the essential introduction to Scandinavian literature and art, one that illuminates the fierce beauty and breathtaking reach of these incomparable works